A Case of Keloids Complicated by Castleman's Disease: Interleukin-6 as a Keloid Risk Factor. Issue 5 (May 2017) - Quong, Whitney L.; Kozai, Yasuji; Ogawa, Rei
Abstract : Summary: Keloids are a manifestation of a fibroproliferative scarring disorder of the skin and develop in response to dermal injury in patients with a susceptible background. Local, systemic, and genetic factors contribute to keloid susceptibility. These factors include tension on the edges of the wound, hormonal influences, and ethnicity, respectively. Castleman's disease is a rare lymphoproliferative disorder that is characterized by the unregulated overproduction of interleukin-6, which leads to systemic lymphadenopathy and constitutional inflammatory symptoms. This case report shows that the bilateral auricular keloids of an adult woman were greatly exacerbated by the onset of Castleman's disease. We present our multimodal management algorithm for auricular keloids, which involves core excision and radiation therapy and achieves excellent aesthetic outcomes. The current treatment pathway for auricular keloids and the possible relationship between interleukin-6 and keloid progression will be discussed.